On the Eve of War Communism: State Food Policy as a Factor of the Russian Grain Market Transformation (February-October 1917) - Rynkov, V. M. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2017)
This article analyses the food policy of the Provisional government within the context of the preceding tsarist and the upcoming Soviet regimes. The topic under consideration is limited to grain, the most important staple food product in Russia of the period in question. The author analyses the grain procurement legislation from November 1916 to September 1918 in detail. Referring to published and archival documents, the author observes consistent intensification of state regulation, and demonstrates that the government’s actions led to a decrease in the production of grain as part of the commodity production system. In spring 1917, the activities of the Provisional government focused on the withdrawal of grain from salespeople and major manufacturers by means of requisition, which contributed to crops reduction in private households, and increased the level of consumption of the crops produced in peasant households. To overcome the negative consequences of inflation and the decline of grain procurement, the Provisional government planned a range of measures that included direct organisation of sowing in large households, the use of private equipment and agricultural machinery by the local population for sowing and harvesting, direct exchange of manufactured goods for grain in order to later withdraw grain stocks from peasants. These measures were not meant for normal market relations between the state and food manufacturers, and could only work due to effective control over peasantry and the use of force. All these measures were further implemented by the Soviet government.